Evaluation of the Bruker MALDI Biotyper for Identification of Fastidious Gram-Negative Rods - Schulthess, Bettina (J Clin Microbiol, 2016)
Matrix-assisted laser desorption ionization−time of flight mass spectrometry (MALDI-TOF MS) has entered clinical laboratories, facilitating identification of bacteria. Here, we evaluated the MALDI Biotyper (Bruker Daltonics) for the identification of fastidious Gram-negative rods (GNR). Three sample preparation methods, direct colony transfer, direct transfer plus on-target formic acid preparation, and ethanol-formic acid extraction, were analyzed for 151 clinical isolates. Direct colony transfer applied with the manufacturer's interpretation criteria resulted in overall species and genus identification rates of 43.0% and 32.5%, respectively; 23.2% of the isolates were not identified, and two misidentifications (1.3%) were observed. The species identification rates increased to 46.4% and 53.7% for direct transfer plus formic acid preparation and ethanol-formic acid extraction, respectively. In addition, we evaluated score value cutoff alterations. The identification rates hardly increased by reducing the genus cutoff, while reducing the 2.0 species cutoff to 1.9 and to 1.8 increased the identification rates to up to 66.2% without increasing the rate of misidentifications. This study shows that fastidious GNR can reliably be identified using the MALDI Biotyper. However, the identification rates do not reach those of nonfastidious GNR such as the Enterobacteriaceae. In addition, two approaches optimizing the identification of fastidious GNR by the MALDI Biotyper were demonstrated: formic acid-based on-target sample treatment and reductions in cutoff scores to increase the species identification rates.